Peran Pembelajaran Kolaboratif dalam Meningkatkan Prestasi Mahasiswa di Akademi Komunitas Negeri Aceh Barat. - Hasan, Riza; Ahkyat, Farthur; Fitrayansyah, Fitrayansyah; Ashwad, Hajar; Masykar, Tanzir (Akademi Komunitas Negeri Aceh Barat, 2024)
Abstract Collaborative learning is an important approach in improving the quality of vocational higher education in the era of globalization. This study aims to analyze the role of collaborative learning in improving student achievement at the Aceh Barat State Community Academy. Using a descriptive qualitative approach, this research involved in-depth interviews, observations, and documentation studies with student and lecturer participants from three D-II study programs. The results showed effective implementation of Project-Based Learning, Problem-Based Learning, and Team-Based Learning models in different study programs. Collaborative learning is proven to improve academic achievement with an increase in average GPA by 0.35 points and an increase in practical skills by 22%. In addition, there were significant improvements in soft skills: communication (28%), teamwork (35%), and problem solving (31%). The main supporting factors include institutional policy support and lecturer readiness, while the main challenges include time constraints and the diversity of student backgrounds. This study concludes that collaborative learning plays an important role in improving the quality of Community Academy graduates, but requires implementation strategies tailored to the context of vocational education. Keywords:Collaborative Learning; Vocational Education; Student AchievementAbstrakPembelajaran kolaboratif menjadi pendekatan penting dalam meningkatkan kualitas pendidikan tinggi vokasi di era globalisasi. Penelitian ini bertujuan menganalisis peran pembelajaran kolaboratif dalam meningkatkan prestasi mahasiswa di Akademi Komunitas Negeri Aceh Barat. Menggunakan pendekatan kualitatif deskriptif, penelitian ini melibatkan wawancara mendalam, observasi, dan studi dokumentasi dengan partisipan mahasiswa dan dosen dari tiga program studi D-II. Hasil penelitian menunjukkan penerapan efektif model Project-Based Learning, Problem-Based Learning, dan Team-Based Learning pada program studi yang berbeda. Pembelajaran kolaboratif terbukti meningkatkan prestasi akademik dengan kenaikan IPK rata-rata sebesar 0,35 poin dan peningkatan keterampilan praktis sebesar 22%. Selain itu, terjadi peningkatan signifikan dalam soft skills: komunikasi (28%), kerja tim (35%), dan pemecahan masalah (31%). Faktor pendukung utama meliputi dukungan kebijakan institusi dan kesiapan dosen, sementara tantangan utama mencakup keterbatasan waktu dan keragaman latar belakang mahasiswa. Penelitian ini menyimpulkan bahwa pembelajaran kolaboratif berperan penting dalam meningkatkan kualitas lulusan Akademi Komunitas, namun memerlukan strategi implementasi yang disesuaikan dengan konteks pendidikan vokasi.